NEMESIS: Keeping Russia an Enemy through Cold War Pathologies - Matthew Crosston (Сравнительная политика, 2015)
This article examines the openly adversarial neoconservative foundation under George Bush to the supposedly more ‘engaged’diplomatic interaction under Barack Obama. What will be exposed is a fairly uninspired and non-innovative American policy that not only fails to consider Russian initiatives from Russia’s own national security perspectives, but aims to contain it within a continued Cold War box that not only sours opportunities for collaboration but guarantees the absence of partnership in areas of global security. This piece examines the consequences of imagining Russia only as nemesis.